Some New Results on Universal Metric Spaces: Akbar Dehghan Nezhad, Najmeh Khajuee, Zead Mustafa - Team, Support (Thai Journal of Mathematics, 2017)
In this paper we establish some common fixed point results for two self-mappings f and g on a universal metric space of dimension n. To prove our results we assume that f is a weakly U-contraction mapping of types A_u and B_u with respect to g. Also we introduce a new concept Γ-distance on a complete partially ordered U_n-metric space and prove a fixed point theorem.